IMPLEMENTASI PROGRAM APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM MENGELOLA KEUANGAN DESA (STUDI KASUS PADA DESA LAMBARO SKEP, KECAMATAN KUTA ALAM, KOTA BANDA ACEH) - Ar-Raniry, Nazarina; Muniruddin, Said (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study discusses the application process of the Village Financial System (Siskeudes) in managing village finances based on Permendagri Number 20 of 2018 concerning Village Financial Management. The research method used is descriptive qualitative. The research location chosen was Lambaro Skep Village, Kuta Alam District, Banda Aceh City. The informants who were the informants in this study were the village head (keuchik), the village secretary, and the head of financial affai rs at Lambaro Skep Village. The data source of this research is primary data obtained from interviews, observations, and documentation. The results showed that the process of implementing Siskeudes in the Lambaro Skep Village Government was carried out based on five stages (planning, implementation, administration, reporting and accountability) and could be said to be successful even though there were still small obstacles in the administration stage and the Siskeudes application also played a role in the process of disbursing village funds.